2016
DOI: 10.1038/ijo.2016.146
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-targeted dodecyltriphenylphosphonium (C12TPP) combats high-fat-diet-induced obesity in mice

Abstract: Background:A membrane-penetrating cation, dodecyltriphenylphosphonium (C12TPP), facilitates the recycling of fatty acids in the artificial lipid membrane and mitochondria. C12TPP can dissipate mitochondrial membrane potential and may affect total energy expenditure and body weight in animals and humans.Methods:We investigated the metabolic effects of C12TPP in isolated brown-fat mitochondria, brown adipocyte cultures and mice in vivo. Experimental approaches included the measurement of oxygen consumption, carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 58 publications
(70 reference statements)
1
21
0
Order By: Relevance
“…437 In fact, TPP + -C 12 was shown to combat high-fat-diet-induced obesity in mice. 440 Several attempts were made to covalently conjugate uncoupling agents to the mitochondria-targeting moiety, in order to improve their efficiency and selectivity and decrease the potential toxicity.…”
Section: Mitochondria-targeted Bioactive Compounds As Potential Thmentioning
confidence: 99%
“…437 In fact, TPP + -C 12 was shown to combat high-fat-diet-induced obesity in mice. 440 Several attempts were made to covalently conjugate uncoupling agents to the mitochondria-targeting moiety, in order to improve their efficiency and selectivity and decrease the potential toxicity.…”
Section: Mitochondria-targeted Bioactive Compounds As Potential Thmentioning
confidence: 99%
“…SkQ1 was further investigated as mitochondria-targeted antioxidant for potential treatment of various age-related diseases, such as Alzheimer's disease [31] or retinopathy [32,33]. Furthermore, a recent study demonstrated that the mitochondrial-targeted C 12 TPP effectively increased oxygen consumption in isolated brown-fat mitochondria, independent of UCP1, and abolished diet-induced obesity in mice by reducing food intake, increasing the resting metabolic rate and overall fatty acid oxidation [34]. In addition, Rhodamine 19 butyl ester (C 4 R1), a short-chain alkyl derivative of Rhodamine 19, was found to decrease the membrane potential and stimulate respiration of isolated liver mitochondria as well as reduce oxidative stress induced by brain ischemia and reperfusion in rats [35].…”
Section: Next Generation Chemical Uncouplersmentioning
confidence: 99%
“…Moreover, in the last decade research focused intensively on the induction of endogenous UCP1 in white adipose tissue depots, also called the "browning" of white fat, and the effects on metabolic health [56,62]. Abbreviations: BAM15, N 5 ,N 6 -bis(2-Fluorophenyl)-oxadiazolo-pyrazine-5,6-diamine [37]; CRMP, controlledreleased mitochondrial protonophore [44]; C 4 R1, Rhodamine 19 butyl ester [36]; C1, nomenclature not defined [38], CZ5, nomenclature not defined [39]; C 12 TPP, dodecyltriphenylphosphonium [34]; FDA, US Food and Drug Administration; DNP, 2,4-dinitrophenol; DNPME, DNP-methylethyl [43]; NEN, niclosamide ethanolamine salt [41]; SkQ1, 10-(6´-plastoquinonyl) decyltriphenylphosphonium) [30]; UCP1, uncoupling protein 1. See text for further details.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Dodecyltriphenylphosphonium (C 12 TPP) has been found to act as an uncoupler, being co-transported with a free fatty acid 23 . The uncoupling activity allows to use this chemical as an anti-obesity drug in murine models 24 . Moreover, lipophilic cations including C 12 TPP appear to be competitive inhibitors of MDR 25 – 27 .…”
Section: Introductionmentioning
confidence: 99%